Comparative proteomic analysis of ovaries from Huoyan geese between pre-laying and laying periods using an iTRAQ-based approach. (1st March 2018) - Cao, Z; Meng, B; Fan, R; Liu, M; Gao, M; Xing, Z; Luan, X
ABSTRACT: To explore the key regulatory genes and their translated products involved in Huoyan goose egg laying, we first applied the iTRAQ technology integrated with LC-MS/MS analysis to identify differentially abundant proteins in the ovarian tissue of Huoyan geese between the pre-laying and laying periods. Then, Gene Ontology (GO) enrichment and Kyoto Encyclopaedia of Genes and Genomes (KEGG) pathway analyses of the proteins were conducted. As observed, 403 proteins, which included 255 up-regulated and 148 down-regulated proteins, were identified. Some differentially abundant proteins, such as apolipoprotein B (apoB), retinol-binding protein 4 (RBP4), vitellogenin-2 (VTG-2), apolipoprotein II (apoVLDL-II), and fatty-acid binding protein 4 (FABP4), were found to be involved in lipid transportation and metabolic process, follicle development and final egg production, ovarian steroidogenesis, and steroid hormone biosynthesis. Subsequently, the modification of the abundance of 3 proteins, adiponectin, FABP4, and RBP4, was verified using Western blotting. Our findings might provide comprehensive protein expression information that can facilitate the understanding of the reproductive biology and improve the egg-laying performance of Huoyan geese.